ON THE ISSUE OF ADMINISTRATIVE AND LEGAL FORMS OF LEGAL SUPPORT OF THE STATUTORY ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that the administrative-legal form is a way of organizing and functioning of state administration, which is based on legal norms and includes the use of administrative means and methods to achieve established goals and objectives. This form regulates relations between the state and citizens, as well as between various authorities. It is noted that the main characteristics of the administrative-legal form are the presence of a clear hierarchy of authorities, the lawful application of administrative procedures and sanctions, as well as ensuring legality and equality before the law. Administrative and legal forms of legal support for the statutory activities of higher education institutions can be classified according to various criteria, including the level of responsibility and competence, specialization of functions, forms of organization and methods of implementation: according to the degree of autonomy, administrative and legal forms can be centralized or decentralized; by level of organization - internal or external; by content - consultative or institutional. With regard to separate administrative-legal forms of legal support for the statutory activities of higher education institutions, attention is focused on the fact that one of the main administrative-legal forms of legal support is the development and analysis of legal documents, such as statutes, regulations, rules, and others. Another form of legal support for the statutory activities of higher education institutions is rulemaking, which plays an important role in regulating their activities, which includes the creation, analysis and improvement of normative legal acts, which are aimed at regulating a wide range of aspects of activities, starting from the organization of management and ending with rights and responsibilities of education seekers and employees. Rulemaking contributes to strengthening the legal foundations of education, protecting the rights and interests of all participants in the educational process, improving the quality of educational services, developing international cooperation, and integrating the Ukrainian higher education system into the global educational space.
Keywords: administrative and legal form; administrative and legal support; legal support; statutory activity; institutions of higher education